Confessions of a Good Arab - Kaniuk, Yoram (New York George Braziller, 1988)
Part Jewish and part Arab, Yosef Rosenzweig/Shehara is torn by the conflict between two peoples, and he comes to realize now much political events shape ones life, regardless of private aspirations
Keywords: Fiction